Response of Endogenous Hormone Concentrations to Two Floral Inductive Treatments, viz. KNO3 and PBZ, in Mango cv. ‘Tommy Atkins’ Growing Under Tropical Conditions - Guevara Berger, Eric (2012)
Floral induction (FI) has been intensively studied in mango, more under sub-tropical than under tropical environments. Decreases in temperature below 20 °C, which is common in sub-tropical regions but seldom occurs in many tropical ones, has been considered a critical factor for FI in this species. Trying to understand the way by which two FI treatments, potassium nitrate (KNO3) and paclobutrazol (PBZ), can regulate flowering by modulating the endogenous concentrations of plant hormones, the following compounds were analyzed in terminal buds, wood and bark sections of lateral branches from treated and untreated ‘Tommy Atkins’ mango trees growing under tropical conditions: indole-acetic acid (IAA), gibberellins (GAs), zeatin/zeatin riboside (Z/ZR) and N 6 (Δ2-isopentenyl) adenine/N 6 (Δ2-isopentenyl) adenosine. Behavior in the contents of these endogenous hormones was often irregular but their course was in general similar for all three treatments. However, levels of GAs were consistently lower in most evaluations of wood and bark sections of PBZ-treated trees compared to KNO3-treated and control plants. In contrast, the endogenous levels of the presumably FI promoting Z/ZR raised considerably at the time close to FI in buds of KNO3-treated trees. These KNO3-treated trees flowered earlier and more profusely than those from other treatments. Although PBZ could be related in this work to a reduction in GA contents, no direct influence of this compound over FI could be established. KNO3 might partially exert its promoting effect on mango FI by increasing Z/ZR contents.